From obligation to opportunity: future of patient-reported outcome measures at the Veterans Health Administration - Coles, Theresa M (Transl Behav Med, 2019)
Patient-reported outcome (PRO) measures are particularly important in mental health services because patients are the central and essential source of information about their mental health status. PRO measures have the potential to engage patients in meaningful and focused conversations during clinical encounters, but unfortunately they often do not serve this purpose in mental health care. Administration of routine outcome measures has often been viewed by clinicians as an obligatory quality improvement process that takes time away from the clinical encounter. This commentary describes current practical barriers to using PRO measures in practice. Then, focusing specifically on the Veterans Health Administration, a unit of the U.S. Department of Veterans Affairs (VA), we propose processes within which PRO measures in mental health services could support the clinical encounter and enhance patient-centered mental health care. With the increasing number of Accountable Care Organizations and other integrated health-care systems that focus on mental health-care delivery, VA has an opportunity to leverage its long-standing electronic medical record technologies and integrated health system to serve as a model for incorporating PRO measures into mental health-care practices. This commentary provides a vision for the future of mental health delivery by incorporating PRO measures at the VA and in other health-care systems.